Impact of Smoking on Oral Mucosa: A Case Report - Nurfianti, Nurfianti; Adinda Rizkhi Nurpratama, Shafa; Audiawati; Ronal, Ahmad; Rokhani, Faezah; Alias, Aspalilah (YARSI Dental Journal, 2024)
Introduction: The discoloration of the oral mucosa is influenced by the presence and degree of dilation of the subepithelial corium blood vessels and the amount of melanin pigment. Changes in the oral mucosa of smokers encompass various significant pathological conditions, including smoker’s melanosis and hyposalivation. Case Report: A 27-year-old male presented to the dental hospital with complaints of black discoloration on the lower jaw gingiva, persisting for the past two years. He exhibited widespread black spots on both the upper and lower jaws without pain. The patient also reported dry lips. He had a smoking history of seven years, with a consumption of 10 cigarettes per day. Examination revealed pigmented lesions, and the patient's stimulated salivary flow rate was 0.7 ml/min. Discussion: The oral cavity is a primary gateway for toxic substances from cigarettes, while saliva is the main biological fluid exposed to cigarette smoke, which contains various toxic compounds responsible for structural and functional changes in saliva. Exposure to cigarette smoke can lead to reduced salivary flow rate (hyposalivation), changes in salivary components that may result in malignancies, and changes in the color characteristics of the oral mucosa, such as the appearance of pigmented lesions known as smoker’s melanosis. Management of hyposalivation in patients includes providing education to improve hydration and encouraging smoking cessation. Conclusion: Smoking affects the condition of an individual's oral cavity, impacting both saliva and the oral mucosa. It is crucial for dentists to educate patients about the use of tobacco and its effects on oral health.